Economic Policy and the Regulation of Corporate Securities. - Austin, Douglas V.; Manne, Henry G. (Journal of Finance, 1971)
The papers in this collection represent the first systematic and comprehensive effort to bring the techniques of economics to bear on a broad spectrum of securities regulation problems.